1995
DOI: 10.1038/nsb0695-504
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Ca2+-free GLA domain sheds light on membrane binding of blood coagulation proteins

Abstract: Reversible membrane binding of gamma-carboxyglutamic acid (Gla)-containing coagulation factors requires Ca(2+)-binding to 10-12 Gla residues. Here we describe the solution structure of the Ca(2+)-free Gla-EGF domain pair of factor x which reveals a striking difference between the Ca(2+)-free and Ca(2+)-loaded forms. In the Ca(2+)-free form Gla residues are exposed to solvent and Phe 4, Leu 5 and Val 8 form a hydrophobic cluster in the interior of the domain. In the Ca(2+)-loaded form Gla residues ligate Ca2+ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
162
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 32 publications
11
162
1
1
Order By: Relevance
“…(2) Insertion of glycine as the fourth residue occurs in factor IX. (3) A cluster of three hydrophobic residues followed by a basic residue (in human factor X, FLyyVK, residues 4~9), which constitute the putative binding site for phospholipids [16], is well conserved in this family but, in factor IX, it is changed to KLwF.._y_v in the human and bovine proteins. It is thus possible that these residues unique to factor IX act as ligands for a Mg 2+ ion, though we cannot exclude possibility of the participation of the C-terminal portion, where some difference is also found.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Insertion of glycine as the fourth residue occurs in factor IX. (3) A cluster of three hydrophobic residues followed by a basic residue (in human factor X, FLyyVK, residues 4~9), which constitute the putative binding site for phospholipids [16], is well conserved in this family but, in factor IX, it is changed to KLwF.._y_v in the human and bovine proteins. It is thus possible that these residues unique to factor IX act as ligands for a Mg 2+ ion, though we cannot exclude possibility of the participation of the C-terminal portion, where some difference is also found.…”
Section: Discussionmentioning
confidence: 99%
“…CHOP was originally identified as a gene induced on DNA damage and growth arrest (Fornace et al 1988). However, subsequent studies have demonstrated a strong correlation between development of ER stress and induction of CHOP (Bartlett et al 1992;Chen et al 1992;Sunnerhagen et al 1995;Carlberg et al 1996;Brewer et al 1997;Dricu et al 1997). CHOP induction closely parallels the time course of BiP induction, where maximal induction occurs after several hours.…”
Section: Er Stress-mediated Induction Of Chop/gadd153 Promotes Apoptosismentioning
confidence: 99%
“…The N-terminal domain, encoded on a separate exon, contains the first 37 amino acid residues including all 10 y-carboxyglutamic acid (Gla) residues [2]. This so-called Gla domain binds seven Ca r+ ions [3,4], an event mediated by the Gla residues, and thereby attains a membrane-interactive ability through the exposure of hydrophobic side chains [4,5]. Studies of the roles of the individual Gla residues in factor IX [6], protein C [7][8][9][10] and prothrombin [11], all of which are homologous to fVII, have been conducted.…”
Section: Introductionmentioning
confidence: 99%